MARKET ANOMAL TESTING REGARDING THE JANUARY EFFECT, ROGALSKI EFFECT AND MONDAY EFFECT IN BANKING SECTOR COMPANIES ON THE INDONESIA STOCK EXCHANGE - Maulana Iqbal; Rico Nur Ilham; Darmawati Muchtar; Widyana Verawaty Siregar (PT. Radja Intercontinental Publishing, 2023)
This study aims to look at market anomalies such as the January effect, Rogalski effect and Monday effect in the banking sub-sector companies in Indonesia. This study uses a quantitative method with an analysis of the Average Difference Test. negative. The Rogalski Effect shows no significant difference when Return is positive or negative. The Monday Effect shows that there is a significant difference in the Monday Effect when the Return is positive or negative.